62 When EPR fixed the protocol problem. (15th December 2021) - Moss, Rachel; Stone, Peter; Eyton-Jones, Penny; Lindsey, Denroy; Gill, Aaron; Cripps, Kelly; Lazareva, Arina; Hill, Annette
Abstract : A Bone Marrow Transplant (BMT) protocol is prepared for each patient with the medical history, preparative regime plus patient & donor details. The protocol is circulated to the MDT prior to the patient admission. The protocol is received in the Transfusion Laboratory by the senior BMS as part of an email distribution list, and the protocol information is entered onto the Laboratory IT System. On this occasion the protocol was not received by the Transfusion Laboratory for a patient who had undergone an ABO mis-matched BMT, and the patient received blood & blood components of their own ABO group for some time after their transplant, and not bi-compatible components as required. Following the incident investigation, it was agreed the current email system was not robust and it was likely this could happen again. A tool within Beacon in Epic was created so that the senior Transfusion BMS sees the BMT protocol prior to distribution, and signs to say it has been checked, or amended if necessary. The process is now as follows: The BMT team fill in their BMT protocol and treatment plan Blood transfusion view the draft protocol PDF (once notified it is ready for review) in Epic and have their own 'mini-form' that they sign to confirm that all details are correct This signature/date will then display in the pdf, and in the BMT database The protocol is not circulated within the multi-disciplinary teams until the transfusion section has been signed. BMT patients by their very nature are complex, and this includes their transfusion requirements. By utilising the EPR system, a process is now in place that has significantly reduced the risk of the Laboratory not being informed of the BMT taking place, and the patient receiving the incorrect components.